Intron-Encoded Domain of Herstatin, An Autoinhibitor of Human Epidermal Growth Factor Receptors, Is Intrinsically Disordered - Tashiro, Daisuke; Suetaka, Shunji; Sato, Nao; Ooka, Koji; Kunihara, Tomoko; Kudo, Hisashi; Inatomi, Junichi; Hayashi, Yuuki; Arai, Munehito (Frontiers in Molecular Biosciences, 2022)
Human epidermal growth factor receptors (HER/ERBB) form dimers that promote cell proliferation, migration, and differentiation, but overexpression of HER proteins results in cancer. Consequently, inhibitors of HER dimerization may function as effective antitumor drugs. An alternatively spliced variant of HER2, called herstatin, is an autoinhibitor of HER proteins, and the intron 8-encoded 79-residue domain of herstatin, called Int8, binds HER family receptors even in isolation. However, the structure of Int8 remains poorly understood. Here, we revealed by circular dichroism, NMR, small-angle X-ray scattering, and structure prediction that isolated Int8 is largely disordered but has a residual helical structure. The radius of gyration of Int8 was almost the same as that of fully unfolded states, although the conformational ensemble of Int8 was less flexible than random coils. These results demonstrate that Int8 is intrinsically disordered. Thus, Int8 is an interesting example of an intrinsically disordered region with tumor-suppressive activity encoded by an intron. Furthermore, we show that the R371I mutant of Int8, which is defective in binding to HER2, is prone to aggregation, providing a rationale for the loss of function.